Ecosocialwork and transformed consciousness: Reflections on eco-mindfulness engagement with the silence of the natural world. Issue 1 (2nd January 2016) - Crews, Douglas; Besthorn, Fred H.
ABSTRACT: Social work has a long history of environmentally and ecologically informed practice. In recent years, the profession has begun to comprehend how environmental crises and global warming impact the clients we serve. What many social workers have come to refer to as ecosocialwork has emerged as a vital new area of social work practice. This article will review the evolution of ecosocialwork. It will suggest that one of the core priorities of ecosocialwork is to assist in the transformation of consciousness toward more earth-friendly actions and attitudes. It will also posit that mindful and purposeful engagement with the silence of the natural world is an important strategy assisting in this transformational process. Finally, it will describe exercises the authors' utilize to assist social work students develop a more mindful engagement with the natural world and offer some implications of eco-mindfulness for social work practice and education.